Delay model for dynamically switching coupled RLC interconnects. Issue 1 (24th April 2014) - Sharma, Devendra Kumar; Kaushik, Brajesh Kumar; Sharma, Rajender Kumar
Abstract : With the evolution of integrated circuit technology, the interconnect parasitics can be the limiting factor in high speed signal transmission. With increasing frequency of operation, length of interconnect and fast transition time of the signal, the RC models are not sufficient to estimate the delay accurately. To mitigate this problem, accurate delay models for coupled interconnects are very much required. This paper proposes an analytical model for estimating propagation delay in lossy coupled RLC interconnect lines for simultaneously switching scenario. To verify the proposed model, the analytical results are compared with those of FDTD and SPICE results for the two cases of inputs switching under consideration. An average error of 2.07% is observed which shows an excellent agreement with SPICE simulation and FDTD computations.